An empirical investigation of failing companies and their determinants using the hazard model in an emerging capital market - Md Rus, Rohani; Abdullah, Nur Adiana Hiau (2005)
The purpose of this study is to highlight the predictors of financial distress during the period 1990 to 2000. Previous studies highlight the inadequacies of the MDA and the log it models and suggest that a hazard model gives a more accurate result due to its consideration of time varying co-variates. By applying the hazard model, we find that leverage, profit, cash flow, liquidity, size and growth play a significant role in explaining financial distress with 83% accuracy rate. This rate did not change much when the model is applied to the hold-out sample. We also find that multicollinearity problem is not a threat in our analysis.